IMPLEMENTASI PEMBELAJARAN TEMATIK INTEGRATIF TEMA “AKU DAN KESEHATANKU” MELALUI PENDEKATAN SAINTIFIK - Abdurrohman, Abdurrohman; Jaelani, Ahmad; S, Nur Eni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Learning with scientific approach, programed by procedure to make students active to construct a concept, law, or principle became a scientist, by means of observed/searched background, problem, formulated problem, formulated hypothesis, collected data with various technique, analyzed data, drawer the conclusion, and shared the result. Furthermore, this research used experiment as a scientific research, it’s mean that the researcher was manipulated and controlled one or more variables, free and observed the related variables to find out the variation that appear simultaneously with manipulated free variables and that variables are influenced and related to the research. Moreover, the research objectives from experiment research, the researcher want to known motive and consequence with used one or more controlled groups without simulation. While, the technic collected data was used observation, test, interview, and documentation. Evaluation stage and scoring a part of students able to accepted the subjects perfectly, such as in cognitive area, the students able to answer ten questions, in psychometric and religious area, the students can be responsible, discipline, and in competent area the students most competent seem from process and representation result.